Modeling dynamic loads on oscillating airfoils with emphasis on dynamic stall vortices - Ayman Mohamed; David H. Wood (Wind Energy, 2021)
Abstract We present a modified version of the ONERA dynamic stall model for improving the prediction of the unsteady forces and load overshoots generated by the shedding of dynamic stall vortices. The modifications include modeling the chord‐axis forces instead of the wind‐axis forces used originally. A novel approach for defining the onset of a dynamic stall is based on the behavior of the chordwise force without correlating the onset empirically. Overshoots in the unsteady aerodynamic loads caused by vortex shedding are modeled by sine‐shaped functions added to the normal force and moment. The onset and duration of these pulses are empirically described in the time domain for convenient use in time‐marching simulations. The modified dynamic stall model is calibrated using a genetic algorithm and compared to experimental data of different airfoils relevant to wind turbine applications. The results show an excellent correlation with the experimental data, particularly in deep dynamic stall, which are characterized by large fluctuations in the aerodynamic loads.